Collective recovery of history from the victims: in Colombia the others also count - González Fonseca , José Guillermo; Sánchez Riaño , Federico (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This research seeks to provide tools for understanding the importance of the collective recovery of history in the construction of a stable peace in Colombia. In the midst of an expected (although uncertain) post-conflict, enunciated in the Peace Agreement signed between the State and the FARC in 2016, transitional justice opens a space to address not only the origin of the conflict and the dark interests that have unloaded its violence against a defenseless population, but also to listen to the voices of the victims.The work addresses the dimensions that this process must take into account based on the categories of memory and history rigorously stated from a collective memory, woven by a society that discovers that others also count. The politics of memory in the framework of a transitional justice emerge as scenarios of endowment of meaning, in constant transformation, determined by social interactions as representations of power.